Dropout in Upper Secondary Education in Mexico : Patterns, Consequences and Possible Causes - Bentaouet Kattan, Raja; Szekely, Miguel (World Bank Group, Washington, DC, 2014)
This study examines the causes and effects of low enrollment and high dropout rates at the upper secondary level in Mexico, where upper secondary completion rates are well below those of other Organisation for Economic Co-operation and Development countries and the regional average. Through a disaggregated analysis of coverage, absorption, and dropout data in secondary education at the state level, the study categorizes states according to the stage in the educational cycle at which dropout primarily occurs. The study further examines the academic, social, and economic consequences of dropout through an analysis of employment and youth survey data. The analysis of factors associated with dropout uses self-reported factors as well as estimated probit models that use household data from national surveys and the national standardized test. The central conclusion reached is that in addition to the patterns of dropout found, multiple elements intersect with the patterns to form a complex panorama. Key findings include: i) personal, family, and household economic factors and the prevalence of social risks have a closer association with dropout earlier in the education cycle; ii) the association between dropout and the quality of education has greater intensity in states where dropout occurs primarily during upper secondary education and in those with the lowest upper secondary dropout rates; and iii) as the returns to education grow, dropout is lower; in the case of returns to higher education, the association with dropout is stronger for states that have the highest dropout during upper secondary education. This complexity merits differentiated responses, which are explored through a brief look at relevant international approaches.